Gender identity and gender fluidity amongst low-income transgender and gender diverse people in the Western Cape, South Africa: Implications for HIV service access - de Villiers, Laing (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.